Application of Progressive Muscle Relaxation Therapy as an Effort to Overcome Anxiety and Stress in RW 11 Community in Gebang Sub-district, Patrang District, Jember: Penerapan Terapi Relaksasi Otot Progresif Sebagai Upaya Mengatasi Kecemasan dan Stres pada Masyarakat RW 11 di kelurahan Gebang Kecamatan Patrang Jember (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2024)
As they get older, most people will inevitably encounter problems in their lives. These things will cause stress, insecurity, emotional, or even loss of motivation in life. The cause of stress can be triggered due to the environment, environmental stressors, physiological, mind, and learning processes. Stress management can be handled with pharmacological and non-pharmacological therapies, one of the decreases in non-pharmacological stress levels is progressive muscle relaxation Progressive muscle relaxation is the simplest and easiest method of relaxation to learn by tensing and relaxing the muscles of the body. This method of community service activities is carried out by providing health education, stress management, and progressive muscle relaxation training to the community. This activity was guided by Ners Professional students and the addition of stress management poster media and progressive muscle relaxation to assist the community in practicing independently. The result of this activity is that people who follow become more relaxed and their anxiety decreases. In addition, this progressive muscle relaxation movement stimulates the release of endorphins that provide a sense of happiness and comfort to the body. The conclusion of this community service activity is to reduce anxiety levels and provide a sense of happiness